Improving the Quality of Life in Perimenopause Through Education on the Use and Processing of Cincau Leaves in Jatinom Village, Blitar Regency - Levi Tina Sari; Handayani; Ita Noviasari; Maria Ulfa; Ika Agustina; Mar'atus Sholichah Fitriah Hajar Kusnianto; Wahyu Wibisono (Journal of Community Service for Health, 2026)
Women entering the perimenopause phase experience fluctuations in the hormones estrogen and progesterone, which can trigger various physical and psychological symptoms, such as hot flashes, sleep disorders, joint pain, mood swings, and even mild depression. Therefore, promotive and preventive efforts are needed to help perimenopausal women maintain their health and well-being. The partners of this community service are the Jatinom village community in Blitar Regency who have entered perimenopause aged 45-55 years, totaling 40 people. The stages of implementing community service are socialization and recruitment, health education as a promotive and preventive measure, processing cincau leaves. These results indicate that education about perimenopausal health and the use of grass jelly leaves has a positive impact on increasing participants' knowledge. Perimenopausal health education and the use of grass jelly leaves, using interactive discussions, leaflets, and videos, have proven effective in increasing public knowledge, particularly regarding efforts to maintain reproductive health during perimenopause.